Electrochemical investigation of cold worked copper in alkaline solution with the presence of potassium ethyl xanthate - Ivanov Svetlana Lj.; Rajčić-Vujasinović Mirjana M.; Petrović Jasmina Lj.; Grekulović Vesna J.; Mladenović Srba A. (Hemijska Industrija, 2014)
This paper presents the investigation results of the electrochemical behavior of copper in 1 M Na2CO3 solution in the presence of potassium ethyl xanthate (KEtX) with different concentrations. Tests were conducted on copper samples obtained without deformation and with deformation of 83, 91 and 99 %. Samples were obtained by cold drawing of wire, which was previously obtained by dip-forming procedure. Corrosion behavior of cold deformed copper wire is characterized by its open circuit potential and behavior during anodic polarization. Experiments were carried out in aqueous solution 1 M Na2CO3 with added various amounts of KEtX between 0.008 g/l and 0.15 g/l. It was experimentally proved that the degree of deformation between 83 and 99 % does not have a large effect on the open circuit potential, as well as on the behavior of copper during anodic polarization in 1 M Na2CO3. Voltammograms show no significant differences between peak heights obtained for different electrodes. The first peak which occurs at potential of around -0.06 V vs. SCE corresponds to the formation of copper oxide Cu2O. The second wide peak is at potential of around 0.15 V vs. SCE and corresponds to the formation of CuO. Addition of potassium ethyl xanthate in alkaline 1 M Na2CO3 solution changes the mechanism of the process in anodic part, which is reflected in the change of shape of voltammograms. In presence of KEtX in concentration between 0.008 g/l and 0.15 g/l on voltammograms a sharp peak appears at potential of about -0.2 V vs. SCE and corresponds to the oxidation of xanthate. Current density, which determines the rate of the process which takes place at the electrode surface, yet in the presence of smallest amounts of KEtX (<0,08 g/l) is higher than in the absence of KEtX. It allows one to conclude that the processes of oxidation of copper accelerate in presence of potassium ethyl xanthate.